PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN INDOSAT BENGKULU - Yulinda, Ade Tiara (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2017)
Ade Tiara Yulinda: The objectives of this research is to analyze the influence of customer relationship management (technology, people, process and knowledge) on customer?s loyalty at PT. Indosat Bengkulu. Using survey research, analysis techniques using a likert scale and using multiple linear regression analysis. Samples used were 100 respondents. The result of this research, can be concluded that the customer relationship management in the variable of technology, people, process, knowledge influenced the loyalty tothe company, and partially the knowledge influenced the loyalty of the customers, while toward the technology, people, process didn?t influence the loyalty of the customers significantly.Key Words : Customer Relationship Management, Technology, People, Process, Knowledge.